THE USE OF ONLINE GAME AS MEDIA TO MOTIVATE LEARNING VOCABULARY IN ENGLISH DURING PANDEMIC AT BAN LOEI WANGSAI SCHOOL THAILAND - Sarah masyitha elysia; Candra Hadi Asmara (Universitas Widyatama, 2022)
This observation ambitions to decide the extent of scholar motivation toward online games in enhancing getting to know English approximately vocabulary. This observation carried out at Ban Loei Wangsai School Thailand. The researcher had 15 students as respondents. The writer uses a qualitative descriptive method with the theories from (Creswell, 2012).The writer also used the theories about the online game to motivate learning vocabulary from Ashraf et al (2014), (Mahmut Kayaalti, 2018) and (Okaz, 2014). Based in the result, it can be visible that college students motivation as 80% of respondents agree that online games encourage college students in getting to know vocabulary, 93% online games are useful tools to be applied in learning vocabulary, 87% online games are effective tools to be applied in learning vocabulary, 73% online games make learning vocabulary more interesting, 87% learning vocabulary using online games become more enjoyable, 67% online games can increase positive feeling, 80% online games can reduce anxiety, 87% online games improve self-confidence in learning vocabulary, 93% learning vocabulary using online games based can create a fun atmosphere in the classroom, 73% online games is a useful tool for improving vocabulary.